2011
DOI: 10.1038/mi.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Mouse and human intestinal immunity: same ballpark, different players; different rules, same score

Abstract: The study of animal immune physiology and animal models of human disease have accelerated many aspects of translational research by allowing direct, definitive investigations. In particular, the use of mice has allowed genetic manipulation, adoptive transfer, immunization, and focused cell and tissue sampling, which would obviously be unthinkable for studies in humans. However, the disease relevance of some animal models may be uncertain and difficulties in interpretation may occur as a consequence of immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
118
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 130 publications
(82 reference statements)
2
118
0
1
Order By: Relevance
“…In the mouse gut, high numbers of CD4 ϩ Th17 cells are already present at steady state. Differentiation of the Th17 cells is directed by retinoic acid-related orphan receptor ROR␥T and driven by the cytokines IL-6 and TGF-␤ (27), all of which were found to have higher gene expression early on in the infection of C57BL/6 mice. In addition, work done by Bienz et al (28) and Zhou et al (29) has revealed that IL-6 plays an important role in controlling acute G. duodenalis infections in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse gut, high numbers of CD4 ϩ Th17 cells are already present at steady state. Differentiation of the Th17 cells is directed by retinoic acid-related orphan receptor ROR␥T and driven by the cytokines IL-6 and TGF-␤ (27), all of which were found to have higher gene expression early on in the infection of C57BL/6 mice. In addition, work done by Bienz et al (28) and Zhou et al (29) has revealed that IL-6 plays an important role in controlling acute G. duodenalis infections in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Walking speed was slower (a; n = 51; p < 0.001), and muscle mass was reduced as measured by leg circumference (b; n = 22, p = 0.05) and by CTdetermined total lean tissue mass measured from both hind limbs (c; n = 27, p = 0.04) in old monkeys. *p < 0.05, ***p < 0.001 2007a; Choi et al, 2012), and this species has comparable intestinal structure and immune function to people (Gibbons and Spencer, 2011). We demonstrate that healthy aging (optimal diet and maintained activity levels) prevents the development of metabolic disease and increases in MT, but does not prevent sarcopenia.…”
Section: Discussionmentioning
confidence: 65%
“…The expression of TLRs on immune cells such as dendritic cells, which strongly dictate the type of immune response induced, and downstream signalling following TLR activation vary considerably between mice and humans (Mestas & Hughes, 2004;Peng, 2005;von Bernuth et al, 2008). In terms of adaptive immunity, their antibody classes and subclasses do not accurately correspond in terms of function and abundance; for example, high concentrations of IgA1 and IgA2 are present in human serum whilst murine IgA is of a single class and present at very low levels in the serum (Gibbons & Spencer, 2011). There is also evidence to suggest that the polarization of T-helper (Th) cell subsets is not as clear cut in humans as it is in mice, and that regulation of Th differentiation may also be different (Gibbons & Spencer, 2011;Mestas & Hughes, 2004).…”
Section: The Immunological Challengesmentioning
confidence: 99%
“…In terms of adaptive immunity, their antibody classes and subclasses do not accurately correspond in terms of function and abundance; for example, high concentrations of IgA1 and IgA2 are present in human serum whilst murine IgA is of a single class and present at very low levels in the serum (Gibbons & Spencer, 2011). There is also evidence to suggest that the polarization of T-helper (Th) cell subsets is not as clear cut in humans as it is in mice, and that regulation of Th differentiation may also be different (Gibbons & Spencer, 2011;Mestas & Hughes, 2004).…”
Section: The Immunological Challengesmentioning
confidence: 99%